The development and use of a model to predict sustainability of change in healthcare settings. (16th March 2011) - Molfenter, Todd; Ford, James H.; Bhattacharya, Abhik
Innovations adopted through organisational change initiatives are often not sustained leading to diminished quality, productivity, and consumer satisfaction. Research explaining variance in the use of adopted innovations in healthcare settings is sparse, suggesting the need for a theoretical model to guide research and practice. In this article, we describe the development of a hybrid conjoint decision theoretic model designed to predict the sustainability of organisational change in healthcare settings. An initial test of the model's predictive validity using expert scored hypothetic profiles resulted in an r-squared value of .77. The test of this model offers a theoretical base for future research on the sustainability of change in healthcare settings.